THE PHYSICAL PREPARATION OF SCHOOL VOLLEYBALL ATHLETES: THE OPTIMIZATION OF STRENGTH AND LOCATED MUSCULAR RESISTANCE ASSOCIATED TO TEENAGERS' HEALTH (Fiep Bulletin - online, 2013)
The practice of volleyball has increased significantly throughout the years, and such factor is also noticeable in school environments, from extra class activities. Within its practice, the sport in question requires a high demand of anaerobic energy sources, based on trainings that involve strength, power and located muscular resistance of the athlete. For the improvement of such inherent aspects during the execution of the basic fundaments of volleyball, the practice of physical preparation becomes indispensable for the optimization of such variables. From these considerations, this paper aims at describing the evolution of the abdominal resistance and the vertical impulsion of 10 volleyball athletes of a school team, aged between 16 and 17 years old, exposed to a physical preparation training based on the development of strength, power and located muscular resistance. From the results achieved, there will be a discussion that focuses not on the benefits that the improvement of the analyzed variables brings to the performance within the game, but a discussion of the results on the improvement of strength, power and located muscular resistance of these teenagers that can be a parameter of health and life quality. This way, this paper aims at discussing the importance of the practice of extra class exercises as a way of keeping the practice of physical exercises among teenagers, fighting sedentarism among school age pupils.
Keywords: health; prevention; physical exercise